Imatinib-Induced Hypogammaglobulinemia in Children and Adolescents with Chronic Myeloid Leukemia. (17th August 2020) - Totadri, Sidharth; Thipparapu, Shankar; Aggarwal, Ritu; Sharma, Madhulika; Naseem, Shano; Jain, Richa; Trehan, Amita; Malhotra, Pankaj; Varma, Neelam; Bansal, Deepak
Abstract: Imatinib-induced tyrosine kinase inhibition extends beyond the BCR-ABL mutation, resulting in adverse effects. We evaluated hypogammaglobulinemia as a potential 'off-target' action of imatinib in children with CML. A cross-sectional, observational study was performed. Patients with CML in chronic phase, age <18-years at diagnosis, receiving imatinib for a duration exceeding 6-months were enrolled. Serum immunoglobulin G, A, and M were measured by end-point nephelometry. Thirty patients were enrolled. The mean age at diagnosis was 10.4 ± 3.1 years (range: 5-18). The mean age at enrollment was 16.4 ± 4.1 years (range: 9-23). The median dose of imatinib was 287.5 mg/m 2 (IQR: 267.3, 345.0). The median duration of imatinib-therapy was 6-years (IQR: 3.0, 10.3). The median (IQR) normalized levels of IgG, IgA, and IgM were 33.0% (IQR: −12.8, 58.7), 28.1% (IQR: −17.0, 90.1) and 15.9% (IQR: −9.3, 40.5), respectively. The IgG, IgA, and IgM levels were reduced in 9 (30%), 8 (27%), and 10 (33%) patients, respectively. Five (17%) patients had pan-hypogammaglobulinemia. We suggest checking immunoglobulin levels in patients with CML receiving imatinib with recurrent/unusual infections.